Islamic Civilization in the Nusantara during Indonesia’s Old Order: Historical Developments and Educational Transformations - A. Faiq Najmil H; Selina Nur Agustin; Siti Asih (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This historical-documentary study examines Islamic education policy and its societal impacts in the Indonesian archipelago during the Old Order period (1945–1966). It aims to analyze how the newly independent Indonesian state institutionalized religious education through the establishment of the Ministry of Religious Affairs, legal recognition of madrasahs, and the development of teacher and judge training programs, including PGA and PHIN. Using qualitative library research, the study drew on primary government documents, legal texts, archival records, and secondary literature, which were analyzed through thematic classification and historical interpretation. The findings reveal persistent tensions between nationalist state-building, reflected in Pancasila-oriented pluralism and Indonesian socialism, and Islamic communities seeking to preserve and modernize pesantren and madrasah traditions. Old Order policies expanded formal access to Islamic education, as shown by the growth of madrasahs and curriculum reforms integrating general and religious subjects. However, implementation remained uneven because of limited funding, political suspicion toward Islamic movements, and divergent visions among state actors, religious scholars, and community organizations. The study further shows that Islamic educational institutions were both preserved and reshaped as they entered the state system, producing important human-capital and cultural contributions while leaving persistent gaps in equity, quality assurance, and curricular harmonization. The study concludes that Islamic education policy during the Old Order played a formative role in defining the relationship between religion, education, and national development in Indonesia. Its implications emphasize the need for policy approaches that respect traditional pedagogies, ensure sustainable funding, and align curricula without eroding the communal and religious functions of Islamic education.